Secured Communication Mechanism For Message Authentication And Data Confidentiality In Secs/Gem Protocol - Jaisan S M, Ashish (2024)
This study proposes SECS/GEM-AE, a mechanism for securing SECS/GEM data messages using AES-GCM encryption and evaluates its performance against the standard SECS/GEM protocol and SECS/GEMsec, a security mechanism proposed to authenticate SECS/GEM messages.